India - Jha, Chandan Kumar; Singh, Vartika; Saxena, Satyam; Ghosh, Ranjan Kumar; Stevanovic, Miodrag (International Institute for Applied Systems Analysis, 2020)
In this second report of the FABLE Consortium, country teams present 20 national pathways towards sustainable land-use and food systems (Figure A). The pathways have been significantly improved since the 2019 report to show how countries can meet mid-century objectives on food security, healthy diets, greenhouse gas emissions, biodiversity, forest conservation, and freshwater use. National FABLE Pathways are consistent with the Sustainable Development Goals (SDGs) and the objectives of the Paris Agreement. They ensure consistent trade flows and can inform long-term climate strategies towards net-zero greenhouse gas emissions under the United Nations Framework Convention on Climate Change (UNFCCC) as well as biodiversity strategies under the Convention on Biological Diversity (CBD).